Formulasi Sediaan Emulgel Ekstrak Daun Tanaman Leunca (Solanum nigrum) Sebagai Antibakteri Staphylococcus aureus pada Kulit - Jon Kenedy Marpaung; Manahan Situmorang; Yanti Musyawarah; Natanael Priltius (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Emulgel is a moisturizing topical preparation that is able to soften the skin and protect it from damage. The leaves of the leunca plant have antibacterial and anti- inflammatory properties. Staphylococcus aureus is a gram-positive bacteria that can be found on human skin. This research aims to find out whether leunca (solanum nigrum) leaf extract can be formulated into an emulgel preparation that meets physicochemical quality, find out whether the resulting emulgel preparation of leunca leaf extract (solanum nigrum) can act as an antibacterial for staphylococcus and find out whether there are differences in the concentration of leunca leaf extract emulgel preparations. (solanum nigrum) affects its effectiveness as an antibacterial for Staphylococcus. This research method used. This research was carried out experimentally with emulgel preparations from leunca leaf extract with concentrations of 2%, 4% and 6% with emulgel evaluation. Based on the experimental results, it was concluded that leunca (solanum nigrum) leaf extract could be formulated F0, F1, F2 and F3 to meet the Organoleptic Test, Homogeneity Test, pH Test, Adhesion Test, Spreadability Test, Viscosity Test and Irritation Test. The emulgel preparation formulation from leunca (solanum nigrum) leaf extract showed potential as an antibacterial for Staphylococcus aureus with a DDH value greater than 20 mm, namely 20,31 to 21,83.